2001
DOI: 10.1136/gut.48.5.714
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency of HLA-DRB1*11 in hepatitis C virus induced end stage liver disease

Abstract: Hepatitis C virus (HCV) infection becomes chronic in more than 70% of patients, leading to end stage liver disease in about 20-30% of these patients. Apart from the virus itself, host factors that modulate the immune response are likely to be involved in determining the outcome of HCV infection. Studies on the association of human leucocyte antigens (HLAs) and HCV infection have shown inconsistent results. Selection of patient subgroups may be crucial. However, any association relevant to HCV disease progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
42
1
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 54 publications
8
42
1
4
Order By: Relevance
“…Minton et al (1998) observed that patients with the HLA-DRB1*11 allele cleared the virus more effectively, and this remained statistically significant even after correction for multiple testing. Similar results have been reported in various other studies (Tillmann et al, 2001;Yenigun & Durupinar, 2002). It is worth mentioning that the HENCORE group did not see any significant association (after Bonferroni correction) between any MHC class II allele and the response of patients to IFN therapy (Thursz et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…Minton et al (1998) observed that patients with the HLA-DRB1*11 allele cleared the virus more effectively, and this remained statistically significant even after correction for multiple testing. Similar results have been reported in various other studies (Tillmann et al, 2001;Yenigun & Durupinar, 2002). It is worth mentioning that the HENCORE group did not see any significant association (after Bonferroni correction) between any MHC class II allele and the response of patients to IFN therapy (Thursz et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…71 Several other groups have studied a variety of alleles, identifying some to be associated with progression and others to be associated with benign chronic liver disease. [72][73][74][75] Other host genetic factors that have been linked to progressive liver fibrosis are polymorphisms in the genes of transforming growth factor-␤1 and angiotensin II. 76,77 Finally, the biochemical expression of chronic HCV infection appears to play a role in disease progression, whether as cause or effect.…”
Section: Factors That Might Have An Impact On the Rate Of Progressionmentioning
confidence: 99%
“…10 Numerous reports have failed to show an association between individual HLA class I antigens and the course of disease in HCV infection. [11][12][13][14] In contrast, several studies have suggested that specific HLA class II alleles may influence outcome parameters in chronic HCV infection such as disease susceptibility, viral clearance, or disease severity. [15][16][17][18][19][20][21] However, many of these studies were small and reported inconsistent findings.…”
mentioning
confidence: 99%